Low-radiation anti-fouling coated glass and preparation method thereof

By using a sandwich structure coating with fluorotantalum doped zinc oxide film-silver film-fluorotantalum zinc oxide film on low-radiation coating glass and applying a functional film, the problem of low-radiation glass being easily adsorbed pollutants when used outdoors is solved. , achieving better low radiation and anti-fouling performance.

CN119219341BActive Publication Date: 2025-02-18LINQU COUNTY SHIAN GLASS PRODUCTS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411765164.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing low-radiation coating glass is prone to absorb dust, water vapor and pollutants in the air when used outdoors, affecting its light transmittance and thermal insulation properties.

Method used

Sandwich structure coating with fluorotantalum doped zinc oxide film-silver film-fluorotantalum zinc oxide film, and the surface is coated with a functional film containing polysiloxane polymer and modified fluorine-containing copolymer to form low radiation protection Stainlessly coated glass.

Benefits of technology

It effectively reduces the heat radiation transmission on the glass surface, improves the low radiation performance, and makes it have good anti-fouling performance by modifying the surface, reducing the adhesion and adsorption of the stain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219341B_ABST
    Figure CN119219341B_ABST
Patent Text Reader

Abstract

The present invention provides a low-radiation anti-fouling coated glass and a preparation method thereof, belonging to the technical field of glass preparation; the preparation process thereof comprises the following steps: preparation of a fluorine-tantalum doped zinc oxide film precursor solution; synthesis of a chain transfer agent; preparation of a modified fluorine-containing copolymer; preparation of a functional film mixed solution; cleaning of a glass substrate; and low-radiation anti-fouling coated glass. The present invention adopts a sandwich structure coating of a zinc oxide film doped with fluorine and tantalum, a silver film, and a zinc oxide film doped with fluorine and tantalum. In the sandwich structure, the silver film is located in the middle layer, and the zinc oxide films doped with fluorine and tantalum are located on both sides. The sandwich structure forms a multilayer film system, which greatly improves the reflectivity of the glass to infrared radiation and achieves a better low-radiation effect. Moreover, the functional film is coated to further achieve a low-radiation effect and increase the anti-fouling ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass preparation, and in particular to a low-radiation anti-fouling coated glass and a preparation method thereof. Background Art

[0002] With the continuous improvement of modern construction technology and people's requirements for living environment, glass is increasingly used in the fields of architecture, automobiles, and electronic equipment. In many application scenarios, the radiation performance and anti-fouling performance of glass have become key considerations.

[0003] Low-emissivity coating technology is a treatment method that coats the glass surface with a metal oxide layer or other compounds. After the glass surface is coated with other metal oxides, it can effectively improve the glass's transmittance to visible light and reflection of mid- and far-infrared light, thereby reducing the heat rise caused by infrared radiation. However, during use, since the surface of low-emissivity glass is exposed to the outdoors for a long time, it is easy to absorb dust, water vapor and various pollutants in the air, which not only affects the aesthetics of the glass, but also further reduces its light transmittance and heat insulation performance. For example, on the curtain wall glass of a building, long-term accumulation of dirt will make the glass look worse, reduce the overall image of the building, and also increase indoor lighting energy consumption due to reduced light transmittance.

[0004] Therefore, we propose a low-emissivity anti-fouling coated glass and a preparation method thereof, which not only has excellent low-emissivity performance but also can effectively prevent the accumulation of dust and stains. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a low-radiation anti-fouling coated glass and a preparation method thereof.

[0006] A method for preparing low-radiation anti-fouling coated glass comprises the following steps:

[0007] S1: Preparation of fluorine-tantalum-doped zinc oxide film precursor solution

[0008] preparing a zinc-containing solution by using zinc acetate and ethylenediamine, and then preparing a tantalum-containing solution and an ammonium fluoride solution, and adding the zinc-containing solution, the tantalum-containing solution and the ammonium fluoride solution into methanol to prepare a precursor solution;

[0009] S2: Synthesis of chain transfer agent

[0010] Dodecanethiol, acetone and methyl trioctyl ammonium chloride are used as raw materials to react to obtain a reaction liquid, the reaction liquid is reacted with a sodium hydroxide aqueous solution, carbon disulfide, acetone and chloroform, and finally deionized water and concentrated acid salt are added to react, filtered, vacuum rotary evaporated, and washed to obtain a chain transfer agent;

[0011] S3: Preparation of modified fluorinated copolymers

[0012] Adding N, N-dimethylaminoethyl methacrylate, a chain transfer agent and azobisisobutyronitrile to tetrahydrofuran to react to obtain a macromolecular chain transfer agent, then adding the macromolecular chain transfer agent, azobisisobutyronitrile and dodecafluoroheptyl methacrylate to acetone to react to prepare a fluorine-containing copolymer, and then modifying the fluorine-containing copolymer with 1-bromooctane to obtain a modified fluorine-containing copolymer;

[0013] S4: Preparation of functional membrane mixture

[0014] A polysiloxane polymer solution is obtained by reacting aminopropyl di-terminated polydimethylsiloxane, tetrahydrofuran solvent and toluene-2,4-diisocyanate, and then titanium dioxide tetrahydrofuran dispersion and modified fluorine-containing copolymer are added and mixed to prepare a functional membrane mixed solution;

[0015] S5: Cleaning of glass substrate

[0016] Performing preliminary cleaning and deep cleaning on the glass to obtain a cleaned glass substrate;

[0017] S6: Low-e anti-fouling coated glass

[0018] The cleaned glass substrate is placed in a reaction chamber, and a precursor solution is atomized and coated, followed by silver deposition, and then a precursor solution is atomized and coated to obtain a sandwich structure coated glass substrate, and a functional film mixed liquid is spin-coated on the sandwich structure coated glass substrate to prepare a glass substrate covered with a functional film, and finally a silicon zirconium aluminum nitride layer is deposited to obtain a low-radiation anti-fouling coated glass.

[0019] Furthermore, step S1 of preparing a fluorine-tantalum-doped zinc oxide film precursor solution specifically includes the following steps:

[0020] S1.1: Add 5-6 parts by weight of zinc acetate and 8-10 parts by weight of ethylenediamine to 20-30 parts by weight of anhydrous ethanol, and stir the mixture at 50-60° C. for 30-40 minutes to obtain a zinc-containing solution;

[0021] S1.2: dissolving 1-2 parts by weight of tantalum pentachloride in 10-12 parts by weight of ethanol solution, stirring to dissolve, to obtain a tantalum-containing solution;

[0022] S1.3: Mix 2-3 parts by weight of ammonium fluoride and 10-12 parts by weight of deionized water to obtain an ammonium fluoride solution;

[0023] S1.4: 0.2-0.3 parts by weight of a tantalum-containing solution, 0.5-0.8 parts by weight of an ammonium fluoride solution and 2-3 parts by weight of a zinc-containing solution are mixed, and then 80-90 parts by weight of methanol are added, and the mixture is stirred and mixed to obtain a precursor solution.

[0024] Furthermore, the synthesis of the chain transfer agent in step S2 specifically comprises the following steps:

[0025] S2.1: Under a nitrogen atmosphere, 20-23 parts by weight of dodecanethiol and 58-60 parts by weight of acetone are added dropwise to 9-10 parts by weight of methyl trioctyl ammonium chloride acetone solution, wherein the weight ratio of methyl trioctyl ammonium chloride to acetone is 1:8-9, and then the mixture is stirred in an ice-water bath to react to obtain a reaction solution;

[0026] S2.2: 8-10 parts by weight of a 50-52wt% aqueous sodium hydroxide solution are added dropwise to the reaction solution, and the reaction is continued for 20-30 min, and then 10-12 parts by weight of acetone and 7-8 parts by weight of carbon disulfide are slowly added, and after mixing, 17-20 parts by weight of chloroform are added, and finally 80-100 parts by weight of a 50-52wt% aqueous sodium hydroxide solution are added dropwise again, and the reaction is stirred for 12-14 h to obtain a reaction mixture;

[0027] S2.3: Add 200-230 parts by weight of deionized water to the reaction mixture, and then add 80-90 parts by weight of concentrated acid salt. After reacting for 5-6 hours, filter the mixture with suction. Dissolve the obtained solid in ethanol and filter it again with suction. Mix the filtrate and perform vacuum rotary evaporation and washing to obtain a chain transfer agent.

[0028] Furthermore, step S3 of preparing the modified fluorinated copolymer specifically comprises the following steps:

[0029] S3.1: 10-12 parts by weight of N, N-dimethylaminoethyl methacrylate, 1-2 parts by weight of a chain transfer agent and 0.5-0.8 parts by weight of azobisisobutyronitrile are added to 20-25 parts by weight of tetrahydrofuran, and reacted at 65-68° C. for 24-25 hours under a nitrogen atmosphere. After the reaction, the reaction is precipitated with n-hexane, and then filtered to obtain a macromolecular chain transfer agent;

[0030] S3.2: 1-2 parts by weight of a macromolecular chain transfer agent, 0.5-0.8 parts by weight of azobisisobutyronitrile and 5-8 parts by weight of dodecafluoroheptyl methacrylate are added to 20-23 parts by weight of acetone, and then reacted at 65-70° C. for 24-25 hours under a nitrogen atmosphere. After the reaction, the mixture is precipitated with n-hexane, and then filtered to obtain a fluorinated copolymer;

[0031] S3.3: Add 1-2 parts by weight of fluorine-containing copolymer and 1.2-1.5 parts by weight of 1-bromooctane to 10-12 parts by weight of dimethylformamide, place at 70-72°C under nitrogen atmosphere to react for 24-25 hours, precipitate with n-hexane after the reaction, and then filter to obtain a modified fluorine-containing polymer.

[0032] Furthermore, the preparation of the functional membrane mixed solution in step S4 specifically includes the following steps:

[0033] S4.1: Dissolve 6-8 parts by weight of 2 mmol aminopropyl dicapped polydimethylsiloxane in 18-20 parts by weight of dry tetrahydrofuran solvent, stir evenly to obtain a silicon solution, then add 0.3-0.5 parts by weight of 2 mmol toluene-2,4-diisocyanate, stir and react for 24-25 hours to obtain a polysiloxane polymer solution;

[0034] S4.2: Concentrate 1-2 parts by weight of polysiloxane polymer solution to a solid content of 30-35wt%, then add 4-5 parts by weight of titanium dioxide tetrahydrofuran dispersion, the weight ratio of titanium dioxide to tetrahydrofuran in the titanium dioxide tetrahydrofuran dispersion is 1:2-3, stir at room temperature to form a homogeneous solution, then add 0.5-0.8 parts by weight of modified fluorine-containing copolymer, stir and mix evenly to obtain a functional membrane mixed solution.

[0035] Furthermore, step S5 of cleaning the glass substrate specifically includes the following steps:

[0036] S5.1: polish one side of the glass to obtain a glass substrate, rinse the glass substrate with tap water for 2-3 times, then soak the glass substrate in a Decon cleaning agent for 20-30 minutes, and perform ultrasonic treatment to obtain a preliminarily cleaned glass substrate;

[0037] S5.2: Rinse the preliminarily cleaned glass substrate with deionized water for 2-3 times, soak the glass substrate rinsed with deionized water in anhydrous ethanol for 20-30 minutes, perform ultrasonic treatment, and then dry it in a drying oven at 50-60° C. to obtain a cleaned glass substrate.

[0038] Furthermore, step S6 of low-radiation anti-fouling coated glass specifically includes the following steps:

[0039] S6.1: Place the cleaned glass substrate in the reaction chamber and heat it to 400-420°C. Then, transport the precursor solution to the atomizer through the peristaltic pump of the atomizer unit. Turn on the atomizer module control switch, drive the atomizer generator to ultrasonically atomize it, introduce carrier gas to transport the atomized particles to the reaction chamber, start reaction deposition for thin film growth, turn off the atomization after 10-12 hours of growth, and then turn off the power and cool it with the furnace to obtain a glass substrate after fluorine tantalum doped zinc oxide coating;

[0040] S6.2: Silver is used as the target, medium frequency power supply, and sputtering pressure is 4×10 -3 mbar, depositing on the surface of the glass substrate coated with fluorine tantalum doped zinc oxide under argon gas to form a silver layer, and then atomizing and coating the precursor solution again according to step S6.1 to obtain a sandwich structure coated glass substrate;

[0041] S6.3: Put the functional film mixture into a spin coater, set the speed to 1200-1300 rpm, the spray gun pressure to 0.2-0.3 MPa, and the spraying time to 15-20 s, spray the functional film mixture on the surface of the sandwich structure coated glass substrate, vacuum dry for 10-12 min, then keep the humidity of the fume hood above 80%, evaporate in the air at room temperature for 1-2 d, and obtain a glass substrate covered with a functional film with a thickness of 50-60 nm;

[0042] S6.4: Using silicon zirconium aluminum nitride layer as target, medium frequency power supply, sputtering pressure of 4×10 -3 mbar, is deposited on the surface of a glass substrate covered with a functional film under argon gas to form a 50-60nm thick silicon zirconium aluminum nitride layer to obtain a low-radiation anti-fouling coated glass.

[0043] Furthermore, in step S6.2, the thickness of each layer of the sandwich structure coating is 30-40 nm, 10-12 nm and 30-40 nm.

[0044] Furthermore, the composition and weight percentage of the silicon-zirconium-aluminum ternary material in the silicon-zirconium-aluminum nitride layer in step S6.4 are: Zr is 12-16%, Al is 5-7%, and the balance is Si.

[0045] A low-radiation anti-fouling coated glass is characterized in that it is prepared by any of the above-mentioned methods for preparing a low-radiation anti-fouling coated glass.

[0046] Compared with the prior art, the present invention has at least the following beneficial effects:

[0047] 1. The polysiloxane polymer solution in the functional film mixed liquid of the present invention has structures such as silicon-oxygen bonds in its molecular chain, which can reflect and absorb electromagnetic waves in the infrared band. The bond energy and vibration frequency of the silicon-oxygen bond make it have a specific absorption peak in the infrared region, which can partially absorb and scatter infrared radiation, thereby reducing the thermal radiation transfer on the glass surface and helping to achieve the low-radiation effect. Titanium dioxide is a good infrared reflective material. When it is mixed with the polysiloxane polymer, it can further enhance the reflection ability of infrared radiation. The high refractive index characteristic of titanium dioxide enables it to change the propagation path of light in the functional film mixed liquid and increase the reflection probability of infrared light, thereby significantly reducing the emissivity of the coated glass and improving its low-radiation performance. In addition, the polysiloxane polymer has a low surface energy. The low surface energy makes the coated glass surface have a certain hydrophobicity. The hydrophobic surface can prevent the attachment of moisture to the glass surface and reduce the adsorption of dirt caused by moisture, thereby achieving an anti-fouling effect.

[0048] 2. The present invention adds a modified fluorine-containing copolymer to the functional membrane mixed liquid. The modified fluorine-containing copolymer contains a variety of fluorine-containing groups. The presence of the fluorine-containing groups reduces the surface energy of the copolymer. The surface with low surface energy makes it difficult for pollutants to adhere, thereby improving the anti-fouling performance. Since the polysiloxane polymer has a lower surface energy, when it is close to the fluorine-containing group of the modified fluorine-containing copolymer, due to the action of intermolecular van der Waals forces, the polysiloxane polymer and the modified fluorine-containing copolymer can be closely arranged at the interface. This close arrangement helps to form a smoother surface, reduce the attachment sites of pollutants, and further promote the anti-fouling performance.

[0049] 3. The present invention dopes fluorine and tantalum into the zinc oxide film. After the tantalum atoms enter the zinc oxide lattice, they occupy the position of the zinc atoms to form substitutional doping, which changes the lattice constant of the zinc oxide and generates lattice strain. When fluorine is doped into the zinc oxide lattice, it causes local contraction of the lattice, further optimizing the crystal structure. The crystal structure of the doped zinc oxide film is more compact and orderly. The co-existence of fluorine and tantalum, as well as the interaction between the two and zinc oxide, can change the crystal orientation and grain size of zinc oxide, making the surface of the film smoother. When light is irradiated onto the glass surface, the flat surface can reduce the scattering of light, improve the transparency and glossiness of the film, increase the reflectivity, and help reduce radiation. In addition, the doping of fluorine can reduce the surface energy of the zinc oxide film, making the surface more hydrophobic. The hydrophobic surface can make water droplets form spheres on the surface, which are easy to roll off and take away the pollutants on the surface. At the same time, it also reduces the adsorption of pollutants on the surface, thereby achieving the purpose of anti-fouling.

[0050] 4. The present invention adopts a sandwich structure coating of zinc oxide film doped with fluorine and tantalum-silver film-zinc oxide film doped with fluorine and tantalum. In the sandwich structure, the silver film is located in the middle layer, and the zinc oxide films doped with fluorine and tantalum are located on both sides. The sandwich structure forms a multi-layer film system. The differences in optical thickness and refractive index between different film layers will produce optical interference, which can cause destructive interference of infrared light of a specific wavelength between film layers, reduce the transmittance of glass to infrared light, and improve infrared reflectivity. Therefore, after the two are combined, the reflectivity of glass to infrared radiation is greatly improved, and a better low-radiation effect is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0052] Figure 1 The present invention is a flowchart of a method for preparing low-emissivity anti-fouling coated glass used in an embodiment of the present invention. DETAILED DESCRIPTION

[0053] The following is a detailed description of a method for preparing a low-radiation anti-fouling coated glass provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0054] Chain transfer agent synthesis route:

[0055]

[0056] Synthesis route of modified fluorinated copolymers:

[0057]

[0058] Example 1

[0059] A method for preparing low-radiation anti-fouling coated glass, such as Figure 1 As shown, the following steps are included:

[0060] S1: Preparation of fluorine-tantalum-doped zinc oxide film precursor solution

[0061] S1.1: Add 5 parts by weight of zinc acetate and 8 parts by weight of ethylenediamine to 20 parts by weight of anhydrous ethanol, and stir the mixture at 50° C. for 30 minutes to obtain a zinc-containing solution;

[0062] S1.2: Dissolve 1 part by weight of tantalum pentachloride in 10 parts by weight of ethanol solution, stir to dissolve, and obtain a tantalum-containing solution;

[0063] S1.3: Mix 2 parts by weight of ammonium fluoride and 10 parts by weight of deionized water to obtain an ammonium fluoride solution;

[0064] S1.4: 0.2 parts by weight of a tantalum-containing solution, 0.5 parts by weight of an ammonium fluoride solution and 2 parts by weight of a zinc-containing solution are mixed, and then 80 parts by weight of methanol are added, and the mixture is stirred to obtain a precursor solution;

[0065] S2: Synthesis of chain transfer agent

[0066] S2.1: Under a nitrogen atmosphere, 20 parts by weight of dodecanethiol and 58 parts by weight of acetone are added dropwise to 9 parts by weight of methyl trioctyl ammonium chloride acetone solution, wherein the weight ratio of methyl trioctyl ammonium chloride to acetone is 1:8, and then the mixture is stirred in an ice-water bath to react to obtain a reaction solution;

[0067] S2.2: 8 parts by weight of a 50 wt% sodium hydroxide aqueous solution was added dropwise to the reaction solution, and the reaction was continued for 20 min, followed by the slow addition of 10 parts by weight of acetone and 7 parts by weight of carbon disulfide, and then 17 parts by weight of chloroform was added after mixing, and finally 80 parts by weight of a 50 wt% sodium hydroxide aqueous solution was added dropwise again, and the reaction was stirred for 12 h to obtain a reaction mixture;

[0068] S2.3: Add 200 parts by weight of deionized water to the reaction mixture, and then add 80 parts by weight of concentrated acid salt, react for 5 hours, filter, dissolve the obtained solid in ethanol and filter again, mix the filtrate, vacuum evaporate and wash to obtain a chain transfer agent;

[0069] S3: Preparation of modified fluorinated copolymers

[0070] S3.1: 10 parts by weight of N, N-dimethylaminoethyl methacrylate, 1 part by weight of a chain transfer agent and 0.5 parts by weight of azobisisobutyronitrile are added to 20 parts by weight of tetrahydrofuran, and reacted at 65° C. for 24 hours under a nitrogen atmosphere. After the reaction, n-hexane is used for precipitation, and then filtered to obtain a macromolecular chain transfer agent;

[0071] S3.2: 1 part by weight of a macromolecular chain transfer agent, 0.5 parts by weight of azobisisobutyronitrile and 5 parts by weight of dodecafluoroheptyl methacrylate are added to 20 parts by weight of acetone, and then reacted at 65° C. for 24 hours under a nitrogen atmosphere. After the reaction, n-hexane is used for precipitation, and then filtered to obtain a fluorinated copolymer;

[0072] S3.3: 1 part by weight of the fluorinated copolymer and 1.2 parts by weight of 1-bromooctane are added to 10 parts by weight of dimethylformamide, and the mixture is reacted at 70° C. for 24 hours under a nitrogen atmosphere. After the reaction, the mixture is precipitated with n-hexane, and then filtered to obtain a modified fluorinated copolymer;

[0073] S4: Preparation of functional membrane mixture

[0074] S4.1: 6 parts by weight of 2 mmol aminopropyl dicapped polydimethylsiloxane was dissolved in 18 parts by weight of dry tetrahydrofuran solvent, and the mixture was stirred to obtain a silicon solution, and then 0.3 parts by weight of 2 mmol toluene-2,4-diisocyanate was added, and the mixture was stirred for 24 hours to obtain a polysiloxane polymer solution;

[0075] S4.2: 1 part by weight of the polysiloxane polymer solution is concentrated to a solid content of 30 wt%, and then 4 parts by weight of a titanium dioxide tetrahydrofuran dispersion is added, wherein the weight ratio of titanium dioxide to tetrahydrofuran in the titanium dioxide tetrahydrofuran dispersion is 1:2, and the mixture is stirred at room temperature to form a homogeneous solution, and then 0.5 parts by weight of a modified fluorine-containing copolymer is added, and the mixture is stirred and mixed uniformly to obtain a functional membrane mixed solution;

[0076] S5: Cleaning of glass substrate

[0077] S5.1: polish one side of the glass to obtain a glass substrate, rinse the glass substrate with tap water twice, then soak the glass substrate in a Decon cleaning agent for 20 minutes, and perform ultrasonic treatment to obtain a preliminarily cleaned glass substrate;

[0078] S5.2: Rinse the preliminarily cleaned glass substrate with deionized water twice, soak the glass substrate rinsed with deionized water in anhydrous ethanol for 20 minutes, perform ultrasonic treatment, and then dry it in a drying oven at 50° C. to obtain a cleaned glass substrate;

[0079] S6: Low-e anti-fouling coated glass

[0080] S6.1: Place the cleaned glass substrate in the reaction chamber and heat it to 400°C. Then, transport the precursor solution to the atomizer through the peristaltic pump of the atomizer unit. Turn on the atomizer module control switch, drive the atomizer generator to ultrasonically atomize it, introduce carrier gas to transport the atomized particles to the reaction chamber, start reaction deposition for thin film growth, turn off the atomization after 10 hours of growth, and then turn off the power and cool it with the furnace to obtain a glass substrate after fluorine tantalum doped zinc oxide coating;

[0081] S6.2: Silver is used as the target, medium frequency power supply, and sputtering pressure is 4×10 -3 mbar, deposited on the surface of the glass substrate coated with fluorine tantalum doped zinc oxide under argon gas to form a silver layer, and then atomized coating of the precursor solution was performed again according to step S6.1 to obtain a sandwich structure coated glass substrate, wherein the thickness of each layer of the sandwich structure coating was 30 nm, 10 nm and 30 nm;

[0082] S6.3: Put the functional film mixture into a spin coater, set the speed to 1200 rpm, the spray gun pressure to 0.2 MPa, and the spraying time to 15 s, spray the functional film mixture on the surface of the sandwich structure coated glass substrate, vacuum dry for 10 min, then keep the humidity of the fume hood above 80%, and evaporate in the air at room temperature for 1 day to obtain a glass substrate covered with a 50 nm thick functional film;

[0083] S6.4: Using silicon zirconium aluminum nitride layer as target, medium frequency power supply, sputtering pressure of 4×10 -3 mbar, and deposited on the surface of a glass substrate covered with a functional film under argon gas to form a 50nm thick silicon zirconium aluminum nitride layer to obtain a low-radiation anti-fouling coated glass.

[0084] The composition and weight percentage of the silicon-zirconium-aluminum ternary material are: Zr is 12%, Al is 5%, and the balance is Si.

[0085] Example 2

[0086] A method for preparing low-radiation anti-fouling coated glass, such as Figure 1 As shown, the following steps are included:

[0087] S1: Preparation of fluorine-tantalum-doped zinc oxide film precursor solution

[0088] S1.1: Add 5 parts by weight of zinc acetate and 8 parts by weight of ethylenediamine to 20 parts by weight of anhydrous ethanol, and stir at 60° C. for 40 minutes to obtain a zinc-containing solution;

[0089] S1.2: Dissolve 1 part by weight of tantalum pentachloride in 10 parts by weight of ethanol solution, stir to dissolve, and obtain a tantalum-containing solution;

[0090] S1.3: Mix 2 parts by weight of ammonium fluoride and 10 parts by weight of deionized water to obtain an ammonium fluoride solution;

[0091] S1.4: 0.2 parts by weight of a tantalum-containing solution, 0.5 parts by weight of an ammonium fluoride solution and 2 parts by weight of a zinc-containing solution are mixed, and then 80 parts by weight of methanol are added, and the mixture is stirred to obtain a precursor solution;

[0092] S2: Synthesis of chain transfer agent

[0093] S2.1: Under a nitrogen atmosphere, 20 parts by weight of dodecanethiol and 58 parts by weight of acetone are added dropwise to 9 parts by weight of methyl trioctyl ammonium chloride acetone solution, wherein the weight ratio of methyl trioctyl ammonium chloride to acetone is 1:8, and then the mixture is stirred in an ice-water bath to react to obtain a reaction solution;

[0094] S2.2: 8 parts by weight of a 50 wt% aqueous sodium hydroxide solution was added dropwise to the reaction solution, and the reaction was continued for 30 min, followed by the slow addition of 10 parts by weight of acetone and 7 parts by weight of carbon disulfide, and then 17 parts by weight of chloroform was added after mixing, and finally 80 parts by weight of a 50 wt% aqueous sodium hydroxide solution was added dropwise again, and the reaction was stirred for 14 h to obtain a reaction mixture;

[0095] S2.3: Add 200 parts by weight of deionized water to the reaction mixture, and then add 80 parts by weight of concentrated acid salt, react for 6 hours, and then filter, dissolve the obtained solid in ethanol and filter again, mix the filtrate, and then vacuum evaporate and wash to obtain a chain transfer agent;

[0096] S3: Preparation of modified fluorinated copolymers

[0097] S3.1: 10 parts by weight of N, N-dimethylaminoethyl methacrylate, 1 part by weight of a chain transfer agent and 0.5 parts by weight of azobisisobutyronitrile are added to 20 parts by weight of tetrahydrofuran, and reacted at 68° C. for 25 hours under a nitrogen atmosphere. After the reaction, n-hexane is used for precipitation, and then filtered to obtain a macromolecular chain transfer agent;

[0098] S3.2: 1 part by weight of a macromolecular chain transfer agent, 0.5 parts by weight of azobisisobutyronitrile and 5 parts by weight of dodecafluoroheptyl methacrylate are added to 20 parts by weight of acetone, and then reacted at 70° C. for 25 hours under a nitrogen atmosphere. After the reaction, n-hexane is used for precipitation, and then filtered to obtain a fluorinated copolymer;

[0099] S3.3: 1 part by weight of the fluorinated copolymer and 1.2 parts by weight of 1-bromooctane are added to 10 parts by weight of dimethylformamide, and the mixture is reacted at 72° C. for 25 hours under a nitrogen atmosphere. After the reaction, the mixture is precipitated with n-hexane, and then filtered to obtain a modified fluorinated copolymer;

[0100] S4: Preparation of functional membrane mixture

[0101] S4.1: 6 parts by weight of 2 mmol aminopropyl dicapped polydimethylsiloxane was dissolved in 18 parts by weight of dry tetrahydrofuran solvent, and the mixture was stirred to obtain a silicon solution, and then 0.3 parts by weight of 2 mmol toluene-2,4-diisocyanate was added, and the mixture was stirred for 25 hours to obtain a polysiloxane polymer solution;

[0102] S4.2: 1 part by weight of the polysiloxane polymer solution is concentrated to a solid content of 30 wt%, and then 4 parts by weight of a titanium dioxide tetrahydrofuran dispersion is added, wherein the weight ratio of titanium dioxide to tetrahydrofuran in the titanium dioxide tetrahydrofuran dispersion is 1:2, and the mixture is stirred at room temperature to form a homogeneous solution, and then 0.5 parts by weight of a modified fluorine-containing copolymer is added, and the mixture is stirred and mixed uniformly to obtain a functional membrane mixed solution;

[0103] S5: Cleaning of glass substrate

[0104] S5.1: polish one side of the glass to obtain a glass substrate, rinse the glass substrate with tap water for 3 times, then soak the glass substrate in a Decon cleaning agent for 30 minutes, and perform ultrasonic treatment to obtain a preliminarily cleaned glass substrate;

[0105] S5.2: Rinse the preliminarily cleaned glass substrate with deionized water for three times, soak the glass substrate rinsed with deionized water in anhydrous ethanol for 30 minutes, perform ultrasonic treatment, and then dry it in a drying oven at 60° C. to obtain a cleaned glass substrate;

[0106] S6: Low-e anti-fouling coated glass

[0107] S6.1: Place the cleaned glass substrate in the reaction chamber and heat it to 420°C. Then, transport the precursor solution to the atomizer through the peristaltic pump of the atomizer unit. Turn on the atomizer module control switch, drive the atomizer generator to ultrasonically atomize it, introduce carrier gas to transport the atomized particles to the reaction chamber, start reaction deposition for thin film growth, turn off the atomization after 12 hours of growth, and then turn off the power and cool it with the furnace to obtain a glass substrate after fluorine tantalum doped zinc oxide coating;

[0108] S6.2: Silver is used as the target, medium frequency power supply, and sputtering pressure is 4×10 -3 mbar, deposited on the surface of the glass substrate coated with fluorine tantalum doped zinc oxide under argon gas to form a silver layer, and then atomized coating of the precursor solution was performed again according to step S6.1 to obtain a sandwich structure coated glass substrate, wherein the thickness of each layer of the sandwich structure coating was 30 nm, 10 nm and 30 nm;

[0109] S6.3: Put the functional film mixed liquid into the spin coater, set the speed to 1300rmp, the spray gun pressure to 0.3MPa, and the spraying time to 20s, spray the functional film mixed liquid on the surface of the sandwich structure coated glass substrate, vacuum dry for 12min, then keep the humidity of the fume hood above 80%, and evaporate in the air at room temperature for 2d to obtain a glass substrate covered with a 60nm thick functional film;

[0110] S6.4: Using silicon zirconium aluminum nitride layer as target, medium frequency power supply, sputtering pressure of 4×10 -3 mbar, and deposited on the surface of a glass substrate covered with a functional film under argon gas to form a 50nm thick silicon zirconium aluminum nitride layer to obtain a low-radiation anti-fouling coated glass.

[0111] The composition and weight percentage of the silicon-zirconium-aluminum ternary material are: Zr is 12%, Al is 5%, and the balance is Si.

[0112] Example 3

[0113] A method for preparing low-radiation anti-fouling coated glass, such as Figure 1 As shown, the following steps are included:

[0114] S1: Preparation of fluorine-tantalum-doped zinc oxide film precursor solution

[0115] S1.1: Add 6 parts by weight of zinc acetate and 10 parts by weight of ethylenediamine to 30 parts by weight of anhydrous ethanol, and stir the mixture at 50° C. for 30 minutes to obtain a zinc-containing solution;

[0116] S1.2: dissolving 2 parts by weight of tantalum pentachloride in 12 parts by weight of ethanol solution, stirring to dissolve, to obtain a tantalum-containing solution;

[0117] S1.3: Mix 3 parts by weight of ammonium fluoride and 12 parts by weight of deionized water to obtain an ammonium fluoride solution;

[0118] S1.4: 0.3 parts by weight of a tantalum-containing solution, 0.8 parts by weight of an ammonium fluoride solution and 3 parts by weight of a zinc-containing solution are mixed, and then 90 parts by weight of methanol are added, and the mixture is stirred to obtain a precursor solution;

[0119] S2: Synthesis of chain transfer agent

[0120] S2.1: Under a nitrogen atmosphere, 23 parts by weight of dodecanethiol and 60 parts by weight of acetone are added dropwise to 10 parts by weight of methyl trioctyl ammonium chloride acetone solution, wherein the weight ratio of methyl trioctyl ammonium chloride to acetone is 1:9, and then the mixture is stirred in an ice-water bath to react to obtain a reaction solution;

[0121] S2.2: 10 parts by weight of a 52 wt% aqueous sodium hydroxide solution was added dropwise to the reaction solution, and the reaction was continued for 20 min. Then, 12 parts by weight of acetone and 8 parts by weight of carbon disulfide were slowly added, and after mixing, 20 parts by weight of chloroform were added. Finally, 100 parts by weight of a 52 wt% aqueous sodium hydroxide solution was added dropwise again, and the reaction was stirred for 12 h to obtain a reaction mixture.

[0122] S2.3: Add 200 parts by weight of deionized water to the reaction mixture, and then add 80 parts by weight of concentrated acid salt, react for 6 hours, and then filter, dissolve the obtained solid in ethanol and filter again, mix the filtrate, and then vacuum evaporate and wash to obtain a chain transfer agent;

[0123] S3: Preparation of modified fluorinated copolymers

[0124] S3.1: 12 parts by weight of N, N-dimethylaminoethyl methacrylate, 2 parts by weight of a chain transfer agent and 0.8 parts by weight of azobisisobutyronitrile are added to 25 parts by weight of tetrahydrofuran, and reacted at 65° C. for 24 hours under a nitrogen atmosphere. After the reaction, n-hexane is used for precipitation, and then filtered to obtain a macromolecular chain transfer agent;

[0125] S3.2: 2 parts by weight of a macromolecular chain transfer agent, 0.8 parts by weight of azobisisobutyronitrile and 8 parts by weight of dodecafluoroheptyl methacrylate are added to 23 parts by weight of acetone, and then reacted at 65° C. for 24 hours under a nitrogen atmosphere. After the reaction, n-hexane is used for precipitation, and then filtered to obtain a fluorinated copolymer;

[0126] S3.3: 2 parts by weight of the fluorinated copolymer and 1.5 parts by weight of 1-bromooctane are added to 12 parts by weight of dimethylformamide, and the mixture is reacted at 70° C. for 24 hours under a nitrogen atmosphere. After the reaction, the mixture is precipitated with n-hexane, and then filtered to obtain a modified fluorinated copolymer;

[0127] S4: Preparation of functional membrane mixture

[0128] S4.1: 8 parts by weight of 2 mmol aminopropyl dicapped polydimethylsiloxane was dissolved in 20 parts by weight of dry tetrahydrofuran solvent, and the mixture was stirred to obtain a silicon solution, and then 0.5 parts by weight of 2 mmol toluene-2,4-diisocyanate was added, and the mixture was stirred for 24 hours to obtain a polysiloxane polymer solution;

[0129] S4.2: 2 parts by weight of the polysiloxane polymer solution is concentrated to a solid content of 35 wt%, and then 5 parts by weight of a titanium dioxide tetrahydrofuran dispersion is added, wherein the weight ratio of titanium dioxide to tetrahydrofuran in the titanium dioxide tetrahydrofuran dispersion is 1:3, and stirred at room temperature to form a homogeneous solution, and then 0.8 parts by weight of a modified fluorine-containing copolymer is added, and the mixture is stirred and mixed uniformly to obtain a functional membrane mixed solution;

[0130] S5: Cleaning of glass substrate

[0131] S5.1: polish one side of the glass to obtain a glass substrate, rinse the glass substrate with tap water twice, then soak the glass substrate in a Decon cleaning agent for 20 minutes, and perform ultrasonic treatment to obtain a preliminarily cleaned glass substrate;

[0132] S5.2: Rinse the preliminarily cleaned glass substrate with deionized water twice, soak the glass substrate rinsed with deionized water in anhydrous ethanol for 20 minutes, perform ultrasonic treatment, and then dry it in a drying oven at 50° C. to obtain a cleaned glass substrate;

[0133] S6: Low-e anti-fouling coated glass

[0134] S6.1: Place the cleaned glass substrate in the reaction chamber and heat it to 400°C. Then, transport the precursor solution to the atomizer through the peristaltic pump of the atomizer unit. Turn on the atomizer module control switch, drive the atomizer generator to ultrasonically atomize it, introduce carrier gas to transport the atomized particles to the reaction chamber, start reaction deposition for thin film growth, turn off the atomization after 10 hours of growth, and then turn off the power and cool it with the furnace to obtain a glass substrate after fluorine tantalum doped zinc oxide coating;

[0135] S6.2: Silver is used as the target, medium frequency power supply, and sputtering pressure is 4×10 -3 mbar, deposited on the surface of the glass substrate coated with fluorine tantalum doped zinc oxide under argon gas to form a silver layer, and then atomized coating of the precursor solution was performed again according to step S6.1 to obtain a sandwich structure coated glass substrate, wherein the thickness of each layer of the sandwich structure coating was 40 nm, 12 nm and 40 nm;

[0136] S6.3: Put the functional film mixture into a spin coater, set the speed to 1200 rpm, the spray gun pressure to 0.2 MPa, and the spraying time to 15 s, spray the functional film mixture on the surface of the sandwich structure coated glass substrate, vacuum dry for 10 min, then keep the humidity of the fume hood above 80%, and evaporate in the air at room temperature for 1 day to obtain a glass substrate covered with a 60 nm thick functional film;

[0137] S6.4: Using silicon zirconium aluminum nitride layer as target, medium frequency power supply, sputtering pressure of 4×10 -3 mbar, and deposited on the surface of a glass substrate covered with a functional film under argon gas to form a 60nm thick silicon zirconium aluminum nitride layer to obtain a low-radiation anti-fouling coated glass.

[0138] The composition and weight percentage of the silicon-zirconium-aluminum ternary material are: Zr is 16%, Al is 7%, and the balance is Si.

[0139] Comparative Example 1

[0140] Compared with Example 1, the difference of Comparative Example 1 is that the tantalum-containing solution in steps S1.2 and S1.4 is removed from Comparative Example 1, and the remaining steps are unchanged to prepare the low-radiation anti-fouling coated glass, which is recorded as Comparative Example 1.

[0141] Comparative Example 2

[0142] Compared with Example 1, the difference of Comparative Example 2 is that the ammonium fluoride solution in steps S1.3 and S1.4 is removed from Comparative Example 2, and the remaining steps are unchanged to prepare the low-emissivity anti-fouling coated glass, which is recorded as Comparative Example 2.

[0143] Comparative Example 3

[0144] Compared with Example 1, the difference of Comparative Example 3 is that, in Comparative Example 3, step S6.2 is removed, and the sandwich structure coated glass substrate in step S6.3 is replaced with a glass substrate coated with fluorine tantalum doped zinc oxide, and the other steps remain unchanged to prepare low-radiation anti-fouling coated glass, which is recorded as Comparative Example 3.

[0145] Comparative Example 4

[0146] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes steps S2-S4 and S6.3, replaces the glass substrate covered with the functional film in S6.4 with a sandwich structure coated glass substrate, and prepares low-radiation anti-fouling coated glass without changing the other steps, which is recorded as Comparative Example 4.

[0147] Comparative Example 5

[0148] Compared with Example 1, the difference of Comparative Example 4 is that, in Comparative Example 5, the modified fluorine-containing copolymer in steps S2-S3 and S4.2 is removed, and the remaining steps remain unchanged to prepare the low-emissivity anti-fouling coated glass, which is recorded as Comparative Example 5.

[0149] Emissivity:

[0150] The emissivity of the low-emissivity anti-fouling coated glass prepared in Examples 1-3 and Comparative Examples 1-4 was measured using an emissivity meter. The measurement structure is shown in Table 1.

[0151] Table 1. Radiation measurement results of Examples 1-3 and Comparative Examples 1-4

[0152]

[0153] It can be seen from the data in Table 1 that the emissivity of Comparative Examples 1 and 2 is higher than that of the embodiment, indicating that the use of zinc oxide film doped with fluorine and tantalum can reduce radiation. The emissivity of Comparative Example 3 is much higher than that of the embodiment, indicating that the sandwich structure coating of zinc oxide film doped with fluorine and tantalum-silver film-zinc oxide film doped with fluorine and tantalum achieves a better low-radiation effect. It can be seen from the data in Comparative Example 4 that coating with a functional film helps to achieve a low-radiation effect.

[0154] Contact Angle:

[0155] A 5 μL droplet (water contact angle is deionized water) was vertically dripped onto the low-emissivity anti-fouling coated glass surface, and the contact angle was measured using a contact angle meter. Contact angle tests were performed on Examples 1-3 and Comparative Examples 2 and 4-5, and the test results are shown in Table 2.

[0156] Table 2. Contact angle test results of Examples 1-3 and Comparative Examples 2 and 4-5

[0157]

[0158] It can be seen from the data in Table 2 that the water contact angle of Comparative Example 2 is lower than that of the embodiment, indicating that fluorine doping can reduce the surface energy of the zinc oxide film, making the surface more hydrophobic and achieving the purpose of anti-fouling. It can be seen from the data of Comparative Examples 4 and 5 that the water contact angle is greatly reduced, indicating that the functional film can make the surface of the coated glass have better hydrophobicity and achieve good anti-fouling effect. At the same time, the added modified fluorine-containing copolymer can further improve the anti-fouling performance.

[0159] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing low-radiation anti-fouling coated glass, characterized in that: The steps include: S1: Preparation of fluorine-tantalum-doped zinc oxide film precursor solution preparing a zinc-containing solution by using zinc acetate and ethylenediamine, and then preparing a tantalum-containing solution and an ammonium fluoride solution, and adding the zinc-containing solution, the tantalum-containing solution and the ammonium fluoride solution into methanol to prepare a precursor solution; S2: Synthesis of chain transfer agent Dodecanethiol, acetone and methyl trioctyl ammonium chloride are used as raw materials to react to obtain a reaction liquid, the reaction liquid is reacted with a sodium hydroxide aqueous solution, carbon disulfide, acetone and chloroform, and finally deionized water and concentrated acid salt are added to react, filtered, vacuum rotary evaporated, and washed to obtain a chain transfer agent; S3: Preparation of modified fluorinated copolymers Adding N, N-dimethylaminoethyl methacrylate, a chain transfer agent and azobisisobutyronitrile to tetrahydrofuran to react to obtain a macromolecular chain transfer agent, then adding the macromolecular chain transfer agent, azobisisobutyronitrile and dodecafluoroheptyl methacrylate to acetone to react to prepare a fluorine-containing copolymer, and then modifying the fluorine-containing copolymer with 1-bromooctane to obtain a modified fluorine-containing copolymer; S4: Preparation of functional membrane mixture A polysiloxane polymer solution is obtained by reacting aminopropyl di-terminated polydimethylsiloxane, tetrahydrofuran solvent and toluene-2,4-diisocyanate, and then titanium dioxide tetrahydrofuran dispersion and modified fluorine-containing copolymer are added and mixed to prepare a functional membrane mixed solution; S5: Cleaning of glass substrate Performing preliminary cleaning and deep cleaning on the glass to obtain a cleaned glass substrate; S6: Low-e anti-fouling coated glass The cleaned glass substrate is placed in a reaction chamber, a precursor solution is atomized and coated, silver is deposited, and then a precursor solution is atomized and coated to obtain a sandwich structure coated glass substrate, a functional film mixed solution is spin-coated on the sandwich structure coated glass substrate to obtain a glass substrate covered with a functional film, and finally a silicon zirconium aluminum nitride layer is deposited to obtain a low-radiation anti-fouling coated glass; Step S1: Preparation of a fluorine-tantalum-doped zinc oxide film precursor solution, specifically comprising the following steps: S1.1: Add 5-6 parts by weight of zinc acetate and 8-10 parts by weight of ethylenediamine to 20-30 parts by weight of anhydrous ethanol, and stir the mixture at 50-60° C. for 30-40 minutes to obtain a zinc-containing solution; S1.2: dissolving 1-2 parts by weight of tantalum pentachloride in 10-12 parts by weight of ethanol solution, stirring to dissolve, to obtain a tantalum-containing solution; S1.3: Mix 2-3 parts by weight of ammonium fluoride and 10-12 parts by weight of deionized water to obtain an ammonium fluoride solution; S1.4: 0.2-0.3 parts by weight of a tantalum-containing solution, 0.5-0.8 parts by weight of an ammonium fluoride solution and 2-3 parts by weight of a zinc-containing solution are mixed, and then 80-90 parts by weight of methanol are added, and the mixture is stirred and mixed to obtain a precursor solution.

2. The method for preparing low-emissivity anti-fouling coated glass according to claim 1, characterized in that: Step S2: Synthesis of chain transfer agent, specifically comprising the following steps: S2.1: Under a nitrogen atmosphere, 20-23 parts by weight of dodecanethiol and 58-60 parts by weight of acetone are added dropwise to 9-10 parts by weight of methyl trioctyl ammonium chloride acetone solution, wherein the weight ratio of methyl trioctyl ammonium chloride to acetone is 1:8-9, and then the mixture is stirred in an ice-water bath to react to obtain a reaction solution; S2.2: 8-10 parts by weight of a 50-52wt% aqueous sodium hydroxide solution are added dropwise to the reaction solution, and the reaction is continued for 20-30 min, and then 10-12 parts by weight of acetone and 7-8 parts by weight of carbon disulfide are slowly added, and after mixing, 17-20 parts by weight of chloroform are added, and finally 80-100 parts by weight of a 50-52wt% aqueous sodium hydroxide solution are added dropwise again, and the reaction is stirred for 12-14 h to obtain a reaction mixture; S2.3: Add 200-230 parts by weight of deionized water to the reaction mixture, and then add 80-90 parts by weight of concentrated acid salt. After reacting for 5-6 hours, filter the mixture with suction. Dissolve the obtained solid in ethanol and filter it again with suction. Mix the filtrate and perform vacuum rotary evaporation and washing to obtain a chain transfer agent.

3. The method for preparing low-emissivity anti-fouling coated glass according to claim 2, characterized in that: Step S3: Preparation of modified fluorinated copolymer, specifically comprising the following steps: S3.1: 10-12 parts by weight of N, N-dimethylaminoethyl methacrylate, 1-2 parts by weight of a chain transfer agent and 0.5-0.8 parts by weight of azobisisobutyronitrile are added to 20-25 parts by weight of tetrahydrofuran, and reacted at 65-68° C. for 24-25 hours under a nitrogen atmosphere. After the reaction, the reaction is precipitated with n-hexane, and then filtered to obtain a macromolecular chain transfer agent; S3.2: 1-2 parts by weight of a macromolecular chain transfer agent, 0.5-0.8 parts by weight of azobisisobutyronitrile and 5-8 parts by weight of dodecafluoroheptyl methacrylate are added to 20-23 parts by weight of acetone, and then reacted at 65-70° C. for 24-25 hours under a nitrogen atmosphere. After the reaction, the mixture is precipitated with n-hexane, and then filtered to obtain a fluorinated copolymer; S3.3: Add 1-2 parts by weight of fluorine-containing copolymer and 1.2-1.5 parts by weight of 1-bromooctane to 10-12 parts by weight of dimethylformamide, place at 70-72°C under nitrogen atmosphere to react for 24-25 hours, precipitate with n-hexane after the reaction, and then filter to obtain a modified fluorine-containing polymer.

4. The method for preparing low-emissivity anti-fouling coated glass according to claim 3, characterized in that: Step S4: Preparation of the functional membrane mixed solution, specifically comprising the following steps: S4.1: Dissolve 6-8 parts by weight of 2 mmol aminopropyl dicapped polydimethylsiloxane in 18-20 parts by weight of dry tetrahydrofuran solvent, stir evenly to obtain a silicon solution, then add 0.3-0.5 parts by weight of 2 mmol toluene-2,4-diisocyanate, stir and react for 24-25 hours to obtain a polysiloxane polymer solution; S4.2: Concentrate 1-2 parts by weight of polysiloxane polymer solution to a solid content of 30-35wt%, then add 4-5 parts by weight of titanium dioxide tetrahydrofuran dispersion, the weight ratio of titanium dioxide to tetrahydrofuran in the titanium dioxide tetrahydrofuran dispersion is 1:2-3, stir at room temperature to form a homogeneous solution, then add 0.5-0.8 parts by weight of modified fluorine-containing copolymer, stir and mix evenly to obtain a functional membrane mixed solution.

5. The method for preparing low-emissivity anti-fouling coated glass according to claim 4, characterized in that: Step S5: cleaning of the glass substrate, specifically comprising the following steps: S5.1: polish one side of the glass to obtain a glass substrate, rinse the glass substrate with tap water for 2-3 times, then soak the glass substrate in a Decon cleaning agent for 20-30 minutes, and perform ultrasonic treatment to obtain a preliminarily cleaned glass substrate; S5.2: Rinse the preliminarily cleaned glass substrate with deionized water for 2-3 times, soak the glass substrate rinsed with deionized water in anhydrous ethanol for 20-30 minutes, perform ultrasonic treatment, and then dry it in a drying oven at 50-60° C. to obtain a cleaned glass substrate.

6. The method for preparing low-emissivity anti-fouling coated glass according to claim 5, characterized in that: Step S6: low-radiation anti-fouling coated glass, specifically comprising the following steps: S6.1: Place the cleaned glass substrate in the reaction chamber and heat it to 400-420°C. Then, transport the precursor solution to the atomizer through the peristaltic pump of the atomizer unit. Turn on the atomizer module control switch, drive the atomizer generator to ultrasonically atomize it, introduce carrier gas to transport the atomized particles to the reaction chamber, start reaction deposition for thin film growth, turn off the atomization after 10-12 hours of growth, and then turn off the power and cool it with the furnace to obtain a glass substrate after fluorine tantalum doped zinc oxide coating; S6.2: Silver is used as the target, medium frequency power supply, and sputtering pressure is 4×10 -3 mbar, depositing on the surface of the glass substrate coated with fluorine tantalum doped zinc oxide under argon gas to form a silver layer, and then atomizing and coating the precursor solution again according to step S6.1 to obtain a sandwich structure coated glass substrate; S6.3: Put the functional film mixture into a spin coater, set the speed to 1200-1300 rpm, the spray gun pressure to 0.2-0.3 MPa, and the spraying time to 15-20 s, spray the functional film mixture on the surface of the sandwich structure coated glass substrate, vacuum dry for 10-12 min, then keep the humidity of the fume hood above 80%, evaporate in the air at room temperature for 1-2 d, and obtain a glass substrate covered with a functional film with a thickness of 50-60 nm; S6.4: Using silicon zirconium aluminum nitride layer as target, medium frequency power supply, sputtering pressure of 4×10 -3 mbar, is deposited on the surface of a glass substrate covered with a functional film under argon gas to form a 50-60nm thick silicon zirconium aluminum nitride layer to obtain a low-radiation anti-fouling coated glass.

7. The method for preparing low-emissivity anti-fouling coated glass according to claim 6, characterized in that: In step S6.2, the thickness of each layer of the sandwich structure coating is 30-40nm, 10-12nm and 30-40nm.

8. The method for preparing low-emissivity anti-fouling coated glass according to claim 6, characterized in that: The composition and weight percentage of the silicon-zirconium-aluminum ternary material in the silicon-zirconium-aluminum nitride layer in step S6.4 are: Zr is 12-16%, Al is 5-7%, and the balance is Si.

9. A low-radiation anti-fouling coated glass, characterized in that: The low-radiation anti-fouling coated glass is prepared by the method for preparing the low-radiation anti-fouling coated glass as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Heat absorption and ultraviolet radiation prevention glass and processing technology thereof

    CN109761505A

  • Coated glass and preparation method thereof

    CN111559875A

  • Glass substrate with film

    CN118401482A